Matrix Metalloproteinase-9 (MMP-9) Levels in Dentinal Fluid as a Diagnostic Biomarker for Irreversible Pulpitis - Megantoro, Aryo; Wairooy, Valeria Widita; Meidyawati, Ratna; Bachtiar, Endang Winiati (Journal of Dentistry Indonesia, 2025)
Objective: Pulpitis is an inflammatory condition of the dental pulp. The inflammatory status can be accurately assessed by histological examination. Biomarkers, such as matrix metalloproteinases (MMPs), are effective indicators of inflammation severity. Among these, matrix metalloproteinase-9 (MMP-9) has emerged as a key mediator of inflammatory processes associated with pulpitis. However, its clinical application as a biomarker remains limited owing to challenges in its extraction. This study aimed to evaluate the effectiveness of MMP-9 extracted from the dentinal fluid as a biomarker for pulpitis. Methods: Dentinal fluid was collected using the blunt tip of a sterile paper point, following clean excavation of the cavities. The paper point was placed in a sterile tube containing phosphate-buffered saline (PBS) and stored at −20 ºC. MMP-9 levels were analyzed using enzyme-linked immunosorbent assay (ELISA). Results: MMP-9 was detected in three of four patients diagnosed with irreversible pulpitis. Kruskal-Wallis test revealed a statistically significant difference in MMP-9 levels in the irreversible pulpitis group (p < 0.05). Conclusion: MMP-9 in dentinal fluid is a potential biomarker for irreversible pulpitis. However, further research is required to validate their diagnostic utility in clinical practice.